ENERGY EFFICIENCY OF FANS FOR LOCAL VENTILATION - Nikolay LAKOV (Fiabilitate şi Durabilitate)
The report examines the issue concerning the energy efficiency of two fans for local airing. A theoretical and experimental study is presented.